PENGELOLAAN ADMINISTRASI DOKUMEN PERKANTORANDENGAN ARSIP ELEKTRONIK PADA PT. INFOMEDIA NUSANTARA JAKARTA - Malau, Yesni (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
Documents administrative management at PT. Infomedia Nusantara is not optimal, where the level of increasing mails volume continuously lead to the equipment and the available storage can no longer accommodate the document. This matter led to the office space look narrower due to the lifting up of the documents.Effects of the accumulation of this document are causing problems. Including the search process documents take a long time because there are so many bundles of documents are untidy.This problem also makes document’s officer hardly to find it. Sometime slipped documents are considered lost. Moreover, the documents are important.Electronic archive applications is a file storage application in electronic form (soft copy), this application is made and can be expected to become solutions. The application is created by web-based, so as to accessible by officers who have been granted access rights in accordance with their duty. Within web-based electronic filing system is expected to make PT.Infomedia Nusantara administrativelyin order, because it will save document storage, enabling archiving, retrieval and distribution of documents, avoiding the uncontrolled destruction of documents and document access rights of the people are not responsible, because with the use of user code and password for each user the appropriate access rights each of the track record of each document can be monitored. In addition to the management and communication processes within the organization will be more effective and efficient.Keyword: Managements, Documents, Administrative